Malignant Extrarenal Rhabdoid Tumor in a 5-Month-Old Male With Mediastinal and Heart/Great Vessel Involvement. (28th October 2020) - Khokhar, H; Craver, R; Stark, M
Abstract: Introduction/Objective: Extrarenal rhabdoid tumor is a high-grade soft-tissue predominately pediatric malignancy with a frequency of 0.15 per million children less than 15 years. It is associated with del(22) (q11.2) with SMARCB1 loss, recognized by loss of INI-1 staining. It has distinct perinuclear hyaline inclusions; however, this feature can be present in other tumors. We describe a malignant extrarenal rhabdoid tumor involving the heart and great vessels to highlight the multiple modalities required for the diagnosis of this tumor in this unusual location. Methods: We utilized routine histology, immunohistochemistry, and electron microscopy. Results: This 5 -month -old male presented with respiratory distress due to a mass that invaded the heart, surrounding the great vessels. The tumor was composed of sheets of polygonal large cells with light pink to clear cytoplasm, eccentric nuclei with mild anisonucleosis, peripherally marginating chromatin, prominent nucleoli, with 2 mitoses per 10 high power field. Hyaline perinuclear inclusions were inapparent. There were frequent clusters of lymphocytes and eosinophils, with 10 percent necrosis and moderately increased vascularity. The tumor was positive for vimentin, SMA, EMA, MSA, S-100, keratin, and WT1, and negative for INI-1, CD34, ALK, AFP, PLAP, CD30, myogenin, NeuN1, synaptophysin, chromogranin, and NSE. Electron microscopy demonstrated occasional cells with perinuclear collections of intermediate filaments, some with whorls. The strong positivity for vimentin, keratin, SMA, MSA, S-100, negative staining for INA-1 and CD34, and visualization of perinuclear intermediate filament whorls by electron microscopy helped make the diagnosis of extrarenal rhabdoid tumor. Conclusion: Malignant extrarenal rhabdomyosarcomas may occur in the middle mediastinum, invade the heart, occur in the first 6 months of life, and not have the typical rhabdoid cells. Diagnoses depend on multiple modalities